Empowering ESL students’ English language proficiency using authentic reading materials in a USR outdoor activity - Wan Mustapha, Wan Zumusni; Syed Ahmad, Tuan Sarifah Aini; Yusuf, Nurul Kamalia; Tengku Mahmod, Tengku Farah Petri; Mohd Mokhtar, Norashikin; Abu Hassim, Aeimi Ruzanna; Ahmad, Irma (2025)
Teaching and motivating secondary school students to read in English Language can be daunting. Therefore, educators of English as a second language are somewhat at a loss to encourage students to read outside the classrooms. This paper shares how second language educators can use authentic reading materials such as Reader's Digest magazine to promote critical reading and creative writing activities among English as a Second Language students in an innovative, critical, fun, and collaborative way outside the classroom. This was done through a university social responsibility (USR) program initiated by the Academy of Language Studies, in collaboration with Reader's Digest magazine. This paper reports a USR program involving 85 secondary students from Sekolah Menengah Agama Nilai, Negeri Sembilan. These students work in groups to do creative writing and critical reading activities outside the classrooms at five checkpoints for two hours. The activities were facilitated by 10 teachers and five lecturers. Findings from the pre- and post-study questionnaires on 85 Form Four and Form Five students show changes in students’ reading interest, confidence, understanding and belief after doing the outdoor reading activities, on top of bringing back the joy of reading.